Teaching Learning Sequence About Green Chemistry and Eco-Batteries: A Results from Qualitative Content Analysis - Octa Ningsi, Rira; Supriatna, Asep; Hernani, ‎; Mudzakir, Ahmad (KnE Social Sciences, 2024)
Batteries can generate electricity as direct current through and electrochemical process called and oxidation-reduction. Batteries can be converted into eco-batteries so that they are able to provide supplies for the community to create energy from renewable sources. This is in accordance to the aspect of green chemistry that can be integrated into learning. This study aims to obtain produce concept maps and Teaching Learning Sequences (TLS) from scientist’s conceptions in the context of eco-batteries. The method used in this research is qualitative content analysis using literature analysis. The literature used in the qualitative content analysis is in the form of textbooks, review articles and research articles. The instrument used in this study includes a content analysis format, which is described descriptively to build students understanding of the principles of green chemistry in the context of eco-batteries. The results showed that the concept map and TLS agreed on the relationship between green chemistry, content and context were found that eco- batteries are an alternative to overcome pollutants from fossil fuels by utilizing the principles of green chemistry. TLS describes the learning flow with several sequencing, 1) fossil fuels, 2) definitions and components in batteries, 3) redox reaction materials 4) examples of Eco-batteries oriented to green chemistry. Eco-batteries in learning can integrate redox concepts that involve aspects of green chemistry, using renewable raw materials and safe chemical products. The results of concept maps and TLS in this study can be used as a basis for designing of teaching material and lesson design. Keywords: Teaching Learning Sequence, Green Chemistry, Eco-Batteries